Non‐targeted hepatitis C virus screening in acute care healthcare settings in the Southern Appalachian region. Issue 5 (12th September 2022) - Chastain, Cody A.; Jenkins, Cathy A.; Rose, Michelle; Moore, Daniel; Parker, Diana; Cave, Barbra; Crowe, Jane; Adams, Sarah; Rubio, Marrieth G.; Potter, Rachel; Quedado, Kimberly; Jones, Ian D.; et al.
Abstract: Objectives: The objective of this study was to evaluate the performance of non‐targeted hepatitis C virus (HCV) screening in emergency departments (EDs) and other healthcare settings in terms of patients identified with HCV infection and linked to HCV care. Methods: In the Southern Appalachian region of the United States, we developed non‐targeted HCV screening and linkage‐to‐care programs in 10 institutions at different healthcare settings, including EDs, outpatient clinics, and inpatient units. Serum samples were tested for HCV antibodies, and if positive, reflexed to HCV ribonucleic acid (RNA) testing as a confirmatory test for active infection. Patients with positive RNA tests were contacted to link them to HCV care. Results: Between 2017 and 2019, among 195, 152 patients screened for HCV infection, 16, 529 (8.5%) were positive by antibody testing, 10, 139 (5.2% of screened patients and 61.3% of patients positive by antibody test) were positive by RNA testing, and 5778 (3.0% of screened patients and 57.0% of patients positive by RNA test) were successfully linked to HCV care. Among 83, 645 patients screened in EDs, 9060 (10.8%) were positive by HCV antibody, and 5243 (6.3%) were positive by RNA test. Among patients positive by RNA testing, linkage to care was lower for patients screened in the ED (44.1%) compared with outpatient clinics (67.6%) ( P < 0.01) and inpatient units (50.9%) ( P < 0.01). Conclusions: Non‐targeted HCV screening in acute care settings can identify large numbers of people with HCV infection. To optimize the utility of these screening programs, future work is needed to develop best practices that consistently link these patients to HCV care.